Elderly women and mental health problems: a qualitative study in Kelantan, Malaysia (Journal of Governance and Development (JGD), 2017)
In the developing world, the disease burden of mental health problems of the aged is associated with demographic and economic change, education, urbanisation, widowhood, war and displacement. In fact, data on nonorganic disorders among the elderly in developing countries are limited and varies by type of mental illness. This situation is influenced by different cultural interpretations of psychiatric disorders. Ageing populations with mental illnesses present additional challenges which are not wellunderstood. This includes concerns about their mental health status and the provision of geriatric services and facilities. These mental health problems need to be well-understood so as to develop appropriate support services and resources. The paper discusses how the caregivers conceptualised mental health problems and their perspectives on the trigger factors linked to mental illness among their older family members. The sampled caregivers reported many different causes of mental illness. Participants were recruited through a psychiatric hospital to ensure that a care recipient has a diagnosis of mental illness. Fourteen Malay caregivers of older people diagnosed with schizophrenia, depression and bipolar disorder were interviewed using semistructured interviews. All interviews were fully transcribed into Malay before being translated into English. All transcriptions were analysed using a thematic analysis supported by the qualitative software (NVivo8). Identifiable themes and patterns of history, symptoms and diagnoses of illness among elderly Malays with a mental health problem were reviewed to develop an overall story. Quotations from all participants are presented in the analysis to maintain rigour and trustworthiness.